Classification and trends in intermittent river flow regimes in Australia, northwestern Europe and USA: A global perspective - Sauquet, Eric; Shanafield, Margaret; Hammond, John C.; Sefton, Catherine; Leigh, Catherine; Datry, Thibault (Journal of hydrology (Amsterdam), 2021)
•A large hydro-climatic dataset was analysed in the context of flow intermittence.•Flow in intermittent rivers varied substantially as a response to aridity.•Many rivers in Australia and USA had upward trends in incidence of no-flow days. This study examines the spatial and temporal variability of flow intermittence over the period 1970–2018 across four countries (Australia, France, UK and the conterminous USA). Intermittence (no-flow periods) in 471 unregulated non-perennial rivers were analyzed using flow data collected from 1356 gauging stations distributed across the four countries. Climate data were also analyzed to place findings within a climate-change context. Intermittence of streamflow demonstrated high seasonality and showed regional differences. An aridity index was the most relevant explanatory factor of flow intermittence at the global scale; the more arid the climate, the higher the probability of non-perennial flow regimes. Flow intermittence was observed, however, in humid climate zones. A global classification of intermittent rivers was developed that included all the facets of the flow regime. This classification served as a basis for trend detection in annual frequency of no flows at the regional scale. Some, but not all, of the 14 examined regions in Australia and the US displayed significant trends and most of them displayed an upward trend in the occurrence of no-flow days.